How Do Foreign Students from Different Collectivist Countries Perceive Interpersonal Emotion Regulation? A Thematic Analysis in Lithuania - Tomas Saulius; Romualdas Malinauskas (Education Sciences)
The main aim of our qualitative research is to find out how foreign students from different Collectivistic countries perceive interpersonal emotion regulation (IER). Using semi-structured interviews as a method of data collection and thematic analysis as a method of data analysis, we found that the majority of participants used IER to provide psychological support to their colleagues and friends in a variety of contexts—64% of participants highlighted cognitive strategies as key in emotional regulation, especially the use of temporal perspective shifting—and that, finally, the majority of the participants highlighted the evident results of the interventions, the most common of which was the increased adaptive behavior of the targets of IER. These findings highlight the persistence of cultural orientation in heterogeneous settings and suggest situational flexibility in IER strategies. They also highlight the importance of designing culturally sensitive interventions in international educational contexts.